Predictive factors in the outcome of pseudocysts complicating alcoholic chronic pancreatitis. Issue 6 (1st December 1997) - Gouyon, B; Lévy, P; Ruszniewski, P; Zins, M; Hammel, P; Vilgrain, V; Sauvanet, A; Belghiti, J; Bernades, P
Abstract : Aims— To determine the clinical, biochemical, and/or morphological features which could predict the need for treatment of pseudocysts at diagnosis in a homogeneous population of patients with alcoholic chronic pancreatitis. Methods— Between January 1983 and December 1993, all patients followed for alcoholic chronic pancreatitis complicated by pseudocysts and confirmed by computed tomography (CT) scan at diagnosis were studied retrospectively. Two groups of pseudocysts were considered according to their pattern of evolution and the therapeutic requirements. Group I included 45 pseudocysts that regressed spontaneously (25 patients) or that persisted without symptoms (20 patients). Group II included 45 pseudocysts with persisting symptoms or complications, requiring surgical or non-surgical treatment. The evolution of pseudocysts was monitored by CT scanning or abdominal ultrasound. Initial CT scans of all patients were reviewed by an experienced radiologist. For each patient with pseudocysts, the following morphological parameters were recorded: number of pseudocysts, maximal diameter, location, intrapancreatic or extrapancreatic development, complications related to the pseudocyst, pancreatic calcifications, enlargement of the main pancreatic duct, and signs of recent acute pancreatitis. Univariate analysis, and then multivariate analysis with all significant variables on univariate analysis were performed. Results— On univariate analysis, location of pseudocysts in the pancreatic head and intrapancreatic development of pseudocysts were significantly more frequent in group I than in group II (78% versus 55%, p<0.02 and 89% versus 60%, p<0.001, respectively). The median diameter of pseudocysts was significantly smaller in group I than in group II (25 (10–110) mm and 40 (10–120) mm respectively, p<0.001). No differences between groups I and II were found for the clinical or biochemical parameters. Multivariate analysis showed that the intrapancreatic development of pseudocysts and a diameter less than 4 cm were the only independent factors associated with a spontaneous and favourable outcome. These factors accounted for 20% of the total variance. Conclusions— Pseudocysts larger than 4 cm and extrapancreatic development can be considered independent predictive factors of persisting symptoms and/or complications in patients with pseudocysts and alcoholic chronic pancreatitis.